Time-Inhomogeneous Feller-Type Diffusion Process in Population Dynamics - Virginia Giorno; Amelia G. Nobile (Mathematics, 2021)
The time-inhomogeneous Feller-type diffusion process, having infinitesimal drift <semantics>α(t)<mspace width="0.166667em"></mspace>x+β(t)</semantics> and infinitesimal variance <semantics>2<mspace width="0.166667em"></mspace>r(t)<mspace width="0.166667em"></mspace>x</semantics>, with a zero-flux condition in the zero-state, is considered. This process is obtained as a continuous approximation of a birth-death process with immigration. The transition probability density function and the related conditional moments, with their asymptotic behaviors, are determined. Special attention is paid to the cases in which the intensity functions <semantics>α(t)</semantics>, <semantics>β(t)</semantics>, <semantics>r(t)</semantics> exhibit some kind of periodicity due to seasonal immigration, regular environmental cycles or random fluctuations. Various numerical computations are performed to illustrate the role played by the periodic functions.